Green and construction supply chain management: The Malaysian scene - Zulhumadi, Faisal; Shafee, Mohd Imran Khusairi; Mohamed Udin, Zulkifli (2010)
Construction industry concerns not only property development but the built-environment as a whole.As the construction industry continues to develop the built environment within the natural environment, stakeholders are accountable to achieve the highest standards of quality, occupational safety and health, and environmental practices.As business operations expand in scope and borders,many successful companies of today are exploring new ways of gaining ground over their competitors in the market. The environmental aspects is considered as one of the key thrusts in the development of the Malaysian construction industry.This paper addresses some issues concerning the applicability of supply chain management in the context of the construction industry, with Malaysia being the backdrop to this research effort.More specifically, this paper will present the results of an initial effort in identifying the awareness level of the key construction industry players, namely the developer/client, contractor, and supplier on the green issue in context of the Construction Supply Chain Management (CSCM).From the results of the study, it was revealed that there were several issues regarding the environment that needs looking at.A discussion based on these findings, which was obtained through a mix of qualitative and quantitative approaches, is also presented. Finally, this paper rounds of the research with a conclusion and some recommendations for future endeavours.